The politics of masculinity: male virility and social coercion in indonesian cinema - Sari, Genny Gustina; Udasmoro, Wening; Noviani, Ratna (Jurnal Komunikasi, 2025)
This article analyzes the representation of male virility as a form of social coercion in two Indonesian films: Test Pack (2012) and Seperti Dendam Rindu Harus Dibayar Tuntas (Vengeance Is Mine, All Others Pay Cash,2021). Drawing on Gunther Kress and Theo van Leeuwen's multimodal discourse analysis, the study explores how the two films construct and critique the pressure on men to prove their masculinity through sexual performance. Although set in different political eras, the Orde Baru and the Reformation, both films depict the penis as a symbolic measure of virility. Characters like Rahmat and Ajo Kawir demonstrate that heterosexual men can also experience subordination due to infertility or impotence, challenging dominant ideals of masculinity. Despite their distinct visual and narrative strategies, the two films reveal how virility operates as a persistent mechanism of social control, shaping male identity across time. These findings underscore the role of cinema in reflecting on and questioning gender norms, particularly ideals surrounding male sexual performance.